Liability of Quasi-Manufacturers for Provision of Information in Disability Accessible Formats in Distance Consumer Contracts – Comparative Perspective - Jintcharadze, Nukri (Teisė, 2025)
This article aims to assess regulations on consumer rights in relation to the provision of information in disability-accessible formats by the relevant Georgian and international legislation in force. In particular, the article, through comparative analysis, describes distinctive matters of combating discrimination in consumer relationships, including case law and regulations of the EU and the United Nations. The article discusses liability of quasi-manufacturers derived from failure to fulfil duties of information in consumer distance contracts concluded with consumers with disabilities. In particular, the article evaluates possibilities of compensation of material and non-material damages. Apart from challenging the issues mentioned above, the article distributes comprehensive study on distinguishing terms ‘clearly personalised’ and ‘disability accessible’ in the light of realization of exceptional withdrawal rights prescribed by directive 2011/83/EU of the European Parliament and of the Council of 25 October 2011 on consumer rights. Accordingly, the article examines the conformity of the Georgian consumer legislation with the respective EU laws under association agreement between Georgia and the European Union.
Keywords: Quasi manufacturer; liability for discrimination; disability accessible formats; information rights of consumers; universal design